The Performance and Characterization of Biodegradable Plastic from Tapioca Starch: Effect of Modified Chitosan - Ernita, Lia; Riza, Medyan; Syaubari, Syaubari (Jurnal Rekayasa Kimia & Lingkungan, 2020)
The performance and characterization of biodegradable plastic from tapioca starch was studied. Modified the chitosan was one of the ingredients for produce the biodegradable plastics. The produced biodegradable polastic were thin sheet plastic, elastic and transparent. The biodegradable plastic performance had tensile strength between 2,26-3.73 Mpa, elongation ranges from 17.24 to 76.76%, and water absorption ranges from 30.81-268.9%. In antioxidant analyze, apples are wrapped in plastic and had significant mechanical properties changes on 8th day.Morphology scanning result showed that in the chitosan-polyNIPAM there were no cavities may caused high hydrophilicity in the biodegradable plastic.